2020
DOI: 10.1002/pbc.28383
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of overall survival in the Collaborative Wilms Tumour Africa Project

Abstract: Introduction The Collaborative Wilms Tumour (WT) Africa Project implemented an adapted WT treatment guideline in six centres in sub‐Saharan Africa. The primary objectives were to describe abandonment of treatment, death during treatment, event‐free survival (EFS) and relapse following implementation. An exploratory objective was to compare outcomes with the baseline evaluation, a historical cohort preceding implementation. Methods The Collaborative WT Africa Project is a multi‐centre prospective clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 12 publications
4
50
0
Order By: Relevance
“… 8 Two-year event-free survival was 49.9% ± 3.8% in this patient cohort when abandonment of treatment was considered an event. 9 The Collaborative Wilms Tumor Africa Project Phase II is planned to start in the second half of 2020 and aims to improve survival further. There are minor revisions to the comprehensive adapted treatment guide-line based on lessons learned in Phase I.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Two-year event-free survival was 49.9% ± 3.8% in this patient cohort when abandonment of treatment was considered an event. 9 The Collaborative Wilms Tumor Africa Project Phase II is planned to start in the second half of 2020 and aims to improve survival further. There are minor revisions to the comprehensive adapted treatment guide-line based on lessons learned in Phase I.…”
mentioning
confidence: 99%
“…After establishing, implementing, and evaluating initial treatment guidelines, we analyzed clinical data and recognized that the major barrier to using more intensive treatment regimens was the lack of optimal supportive care. 9 In 2019, Supportive Care for Children With Cancer in Africa (SUCCOUR) was initiated, with a goal to improve supportive care and reduce treatment-related mortality further. Building on the regional network of the Collaborative Wilms Tumor Africa Project and the lessons learned, SUCCOUR aims to promote improvements in supportive care for every child in Africa to be able to be cured from cancer.…”
mentioning
confidence: 99%
“…Close Follow-up, including home visits when needed, might reduce this problem 21 . Chagaluka et al 22 found that funds used to cover treatment, travel, and other associated costs for patients, significantly reduced the abandonment rate. In our setting, a different approach to minimize abandonment might be more useful.…”
Section: Discussionmentioning
confidence: 99%
“…Using this multi-center regional collaborative network, program implementation was associated with significantly higher survival without evidence of disease at the end of treatment compared to baseline evaluations (68.5% vs. 52%) (26)(27)(28). Financial support for medical treatment was highlighted as a key strategy to decrease abandonment of treatment (28). In the first multicenter prospective study in sub-Saharan Africa, seven units participated from Senegal, Madagascar, Cameroon, Cote d'Ivoire, Mali, Togo, and Burkina Faso.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…The principal aim was to decrease abandonment of treatment and to improve outcomes (26). Using this multi-center regional collaborative network, program implementation was associated with significantly higher survival without evidence of disease at the end of treatment compared to baseline evaluations (68.5% vs. 52%) (26)(27)(28). Financial support for medical treatment was highlighted as a key strategy to decrease abandonment of treatment (28).…”
Section: Social Determinants Of Healthmentioning
confidence: 99%